Pengangkatan Anak serta Implikasinya Terhadap Nasab, Hadanah, Nafkah dan Pusaka dalam Undang-Undang Keluarga Islam: Child Adoption and Its Implications Towards Paternity, Custody, Maintenance and Inheritance in Islamic Family Law - Noor, Zanariah; Opir, Anhar (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2017)
Child adoption is permissible in Islam, and even in the case of an orphan this practice is encouraged. This practice has its advantages for it allows protection towards those in needs in the society. The adopted child does not become a “true child” of the adoptive parents, thus an interaction between adoptive parents and the adopted child as well as other aspects such as paternity (as in the case of naming the child to his/her own biological father), limit of interactions as well as inheritance that arose from this relationship should be observed. This writing applies content analysis technique which provides insight from Islamic jurisprudence scholars’ views regarding child adoption and it implications on paternity, custody, maintenance and inheritance as well as provisions of law regarding those matters in Malaysia. Decided cases heard in Shariah Court which had applied law provisions as well as the application of Islamic jurisprudence principle would also be highlighted.